The Role of School Principals in Conflict Mediation and Policy Negotiation with Teachers at SMP Negeri 1 Parigi - Mutiara Anjani; Annisa Nurahmayanti; Barizah Amalia (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
This study aims to examine the role of school principals in conflict mediation and policy negotiations with teachers at SMP Negeri 1 Parigi. School principals play a key role in creating a harmonious and effective work environment in mediating conflicts and formulating policies that involve various parties, especially teachers. Conflicts that occur in schools can be interpersonal or structural, while negotiated policies involve various aspects of school management, such as curriculum, student assessment, and the division of teaching tasks. Through a qualitative approach, this study collects data through interviews with principals and teachers involved in conflict and policy negotiations. The results of the study show that the principal at SMP Negeri 1 Parigi acts as a wise mediator and facilitator by using a restorative and participatory approach. Transformational leadership implemented by school principals has succeeded in creating a more open and cooperative work environment, reducing conflict, and increasing teacher productivity. In addition, negotiation strategies based on open communication and compromise increase agreement and support for implemented policies. The impact of this mediation and negotiation is very positive, strengthening the relationship between teachers and principals, and improving the quality of policy implementation. This research makes an important contribution to the development of education management and provides guidance for school principals in improving leadership capacity and managing work relationships in schools.